Assessment of Time and Frequency Domain Parameters of Heart Rate Variability and Interictal Cardiac Rhythm Abnormalities in Drug-naïve Patients with Idiopathic Generalized Epilepsy - ÇİNÇİN, AHMET ALTUĞ; KEPEZ, ALPER; MİDİ, İPEK; AĞAN YILDIRIM, KADRİYE (My University, 2016)
BACKGROUND AND PURPOSE: Epilepsy is a disease known to occur with autonomous phenomenons. Earlier studies indicate decreased heart rate variability (HRV) during ictal and interictal periods among epilepsy patients. In this study, we aim to investigate cardiac rhythm abnormalities and HRV during interictal period between drug-naïve patients with idiopathic generalized epilepsy (IGE) and healthy control group. METHODS: Twenty-six patients with IGE and 26 healthy individuals included in the study. In order to eliminate any structural cardiac pathology, transthoracic echocardiography was performed in all subjects and time and frequency domain parameters of HRV were evaluated after 24-hour rhythm holter monitoring. RESULTS: Between two groups, no significant difference was detected in terms of mean heart rate and maximum duration between the start of the Q waves and the end of the T waves (QT intervals). In the time domain analysis of HRV, no statically significant difference was detected for standard deviation of all R - R intervals and root-mean-square of successive differences between patient and control group (p = 0,070 and p = 0,104 respectively). In the frequency domain analysis of HRV, patients tended to display lower total power and very low frequency power than did healthy subjects, but the differences were not statistically significant. CONCLUSIONS: Our results suggest that there is no major effect of the epilepsy on HRV in patients with IGE. It should be emphasized that, in this study, HRV was evaluated only in patients with IGE and that the results are not proper to be generalized for patients with partial seizures.
Keywords: Autonomic control; Cardiac rhythm; Epilepsy; Heart rate/physiology